Evaluation of implementation and satisfaction of distance learning among medical students during COVID-19 pandemic in Indonesia - Wiranto, Rony; Syakurah, Rizma Adlia (International Journal of Research in Medical Sciences, 2020)
Background: Since it was declared as a pandemic by the world health organization (WHO) on March 11th, 2020, COVID-19 has become a global health problem in the world. The temporary closure of schools and universities was carried out to protect teachers and students from viruses, including in medical schools. Distance learning has been implemented as an alternative to subtitute conventional class. This can affect the satisfaction of medical students toward it. This study aim was to evaluating implementation and analyzing the factors that influence medical student’ satisfaction toward distance learning during the COVID-19 pandemic. Methods: An observational analytic study with a cross-sectional study was used. A total of 3331 respondents from all over Indonesia responded through an online questionnaire by Ikatan Senat Mahasiswa Kedokteran Indonesia (ISMKI) distributed from April 9th, 2020 to June 21st, 2020. Data analyzed using chi-square test (alternative: fisher exact test) and logistic regression with significance alpha=0.05. Results: Study showed that most respondents had difficulties in learning and had less satisfaction toward distance learning. Factors that showed statistical significance were university origin grouped by type, region, accreditation, and readiness. Conclusions: Although distance learning is a solution to the problems of medical education during this pandemic, the government and related institutions should be able to continue evaluating so that the learning system remains effective and efficient.